Peningkatan Kepedulian Sosial Remaja di Asrama Putera Monte Carmelo Maumere melalui Kegiatan PKM Berbasis Karakter - Marthen Preskapu Wela; Christian Romario; Arianto Marselino Hode; Maria Alexandra Wea (BALE LITERASI, 2026)
Adolescents living in male dormitories experience complex social dynamics; however, apathetic attitudes are still commonly found, characterized by low social awareness, lack of participation in collective activities, and limited empathy toward others. This community service program aims to enhance adolescents’ social awareness through a character-based approach. The method employed was a participatory approach consisting of initial observation, counseling sessions, group discussions, and social activities such as communal work and collaborative tasks. Evaluation was conducted using pre-test and post-test questionnaires, behavioral observation, and activity documentation. The results indicate an increase in the average social awareness score from 32.7 to 53.9, with a percentage increase of 64.8%. In addition, observable behavioral changes were found, including improved participation, cooperation, and concern for the dormitory environment. The findings suggest that a participatory character-based approach is effective in fostering adolescents’ social awareness. Therefore, this community service program can serve as an alternative model for character development in male dormitory environments.